Publisher Correction: A functional variant in the OAS1 gene is associated with Sjögren's syndrome complicated with HBV infection. Issue 1 (December 2018) - Liu, Xianjun; Xing, Hongcun; Gao, Wenjing; Yu, Di; Zhao, Yuming; Shi, Xiaoju; Zhang, Kun; Li, Pingya; Yu, Jiaao; Xu, Wei; Shan, Hongli; Zhang, Kaiyu; et al.
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has been fixed in the paper.